(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Recurrences have been a significant problem following hernia repair. Prosthetic materials are increasingly used in hernia repair to prevent recurrences. Their use has been associated with several advantages, such as less postoperative pain, rapid recovery and low recurrence rates. Objectives: This study has been done to find out the early and late morbidity specially the recurrence rates of Hernia after mesh hernioplasty. Methods: This retrospective study, was performed on 100 patients between the periods of October 2007 to October 2012 at Combined Military Hospital, Dhaka, on whom tension free open repair were performed by Rives (Inlay), Lichtenstein (onlay) or Stoppa (GPRVS) technique. Stoppa technique was applied in bilateral cases. Laparoscopic inguinal hernia repair was done by TAPP (Trans Abdominal Pre Peritoneal) approach. All data concerning age, sex, history, and symptoms of patients, as well as the post operative condition of the patients were recorded in predesigned data sheet. Results: Out of 100 cases 90 (90%) were male and 10 (10%) were female. The overall age ranged between 30 80 years with an increased incidence between 5th and 6th decades (50%). Most of the patients were having inguinal Hernia (75%), 83 JAFMC Bangladesh. Vol 9, No 2 (December) 2013 followed by incisional hernia in 15 (15%) and paraumbilical hernia in 10 (10%) patients. Among inguinal hernia, direct variety were 53 (58.2%), indirect 29 (31.9%), recurrent 9 (9.9%), right sided 44 (48.3%), left sided 31 (34.1%) and bilateral 16 (17.6%). Fifteen (15%) cases had diabetes mellitus, 10 (10%) cases had hypertension, 12 (12%) cases had been suffering from bronchial asthma and 2 (2%) cases had features of prostatism. Ninety two (92%) patients underwent open surgery and 8 (8%) cases laparoscopic hernioplasty. Among the open procedure done (83 procedures) in inguinal hernias unilateral inlay inguinal hernioplasty (Rives) was done in 47 (56.6%), onlay (Lichtenstein) in 20 (24.1%) and Stoppa procedure was done in 16 (19.3%) bilateral cases. In all 100 cases, a sheet of Polypropyelene mesh was given as prosthetic material. Post operatively a few patients developed complication. Ecchymosis of skin in 2 (2%), testicular swelling and orchitis in 4 (4%), wound infection in 3 (3%), retention of urine in 10 (10%) cases. All were treated and improved. 2 (2%) cases developed recurrence after operation as found in follow-up where onlay mesh were given and who had features of prostatism. Conclusion: Tension-free mesh hernia repair is a simple, safe, comfortable and effective method, with extremely low early and late morbidity and remarkably low recurrence rate and therefore it is a preferred method for hernia repair. DOI: http://dx.doi.org/10.3329/jafmc.v9i2.21842 Journal of Armed Forces Medical College Bangladesh Vol.9(2) 2013